Agro-economic performance of arugula fertilized with chicken manure - Oliveira, Witor Marcelo da Silva; Silva, Antônio Gideilson Correia da; Fernandes, Gabriel Kariel Ferreira; Bento, José Elinaldo Alves; Silva, Maurício dos Santos; Lima, Jailma Suerda Silva de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2024)
The arugula is a vegetable widely consumed by the Brazilian population due to its spicy flavor, captivating odor, high dietary value, and being a source of vitamins and minerals. It is a leafy green much appreciated by consumers who seek a healthy diet. To evaluate the agro-economic performance of arugula fertilized with different amounts of chicken manure, research was conducted at the “Rafael Fernandes” Experimental Farm in the district of Lagoinha, Mossoró, Rio Grande do Norte, from July to September 2019. The experimental design used was a randomized complete block design with 4 treatments and four replications. The treatments consisted of four quantities of chicken manure (5, 10, 20, and 40 t ha-¹) on a dry basis. The characteristics evaluated were plant height, number of leaves, yield of fresh and dry mass of the aerial part. The economic indices evaluated such as gross income, net income, return rate, and profitability index. The quantities of chicken manure influenced the performance of the arugula, with the greatest plant height, fresh mass yield, and dry mass yield of the aerial part obtained at 40 t ha-¹ incorporated into the soil. The number of leaves was not influenced by the tested quantities. The greatest agro-economic efficiency obtained for arugula cultivation was with the use of chicken manure in the quantity of 40 t ha-¹.